Successful esophageal endoscopic submucosal dissection with intraoperative release of stenosis due to previous endoscopic submucosal dissection scarring. Issue 1 (6th January 2022) - Ishii, Rindo; Ohata, Ken; Sawada, Rikimaru; Takeuchi, Nao; Kurebayashi, Marie; Inamoto, Rin; Takayanagi, Syunya; Kimoto, Yoshiaki; Nohara, Mako; Liu, Bo; Negishi, Ryoju; Minato, Yohei; et al.
Abstract: Endoscopic submucosal dissection (ESD) is the standard endoscopic treatment for early esophageal cancer. Esophageal stricture often occurs at the site of ESD for large lesions. When treating a metachronous lesion appearing at the severe stricture, it may be difficult to negotiate a conventional endoscope through the stricture. Using a thin endoscope may be a useful strategy for such lesions, though ESD using a thin endoscope is challenging because of poor maneuverability. Herein, we report a case of successful ESD for early esophageal cancer at the severe stricture, using a conventional endoscope. A 72‐year‐old man with a previous history of ESD for esophageal cancer and a post‐ESD esophageal stricture was referred to our hospital for metachronous early esophageal cancer. The lesion, 10 mm in diameter, was located at the stricture with a slight distal extension. Conventional endoscopes could not be negotiated through stricture. Therefore, submucosal dissection was performed from the oral to the anal aspect of the lesion, as far as possible. After completion of submucosal dissection of the oral aspect of the lesion and part of the lesion located on the stricture, the severe stricture was released, allowing the passage of conventional endoscope, and ESD of the entire lesion was completed en bloc. Histopathological examination showed squamous cell carcinoma, pT1a‐LPM. Stricture due to scarring may occur during the regeneration process of the defective mucosa, muscularis mucosa, and submucosal layer. Therefore, incision and dissection of the contracted mucosa, mucularis mucosa, and submucosal layer would release the stenosis.